2018
DOI: 10.31018/jans.v10i1.1575
|View full text |Cite
|
Sign up to set email alerts
|

Effect of storage period on internal and external parameters of Deshi Chicken fowl

Abstract: Abstract:The fresh eggs were collected and evaluated to effect of storage periods on internal and external characteristics in local chicken eggs. The data from current study indicates that with increase in storage period, a significant (P<0.01) decline was observed in various parameters like percentage weight loss, albumen height, yolk height, egg width, albumen index, yolk index, Haugh unit, albumen %, albumen weight, shell thickness and albumen protein. Contrary to this, albumen pH (P<0.01) was found to esca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 5 publications
(8 reference statements)
1
2
0
Order By: Relevance
“…Earlier, Alleoni and Antunes (2001) came to a comparable conclusion that HU and H "decreased significantly during storage." Similar trends in changes in egg white indicators have been confirmed, probably, by all researchers who have studied this issue (Karoui et al, 2006;Khan et al, 2014;Lall et al, 2018;Samli et al, 2005;Tabidi, 2011).…”
Section: Introductionsupporting
confidence: 70%
“…Earlier, Alleoni and Antunes (2001) came to a comparable conclusion that HU and H "decreased significantly during storage." Similar trends in changes in egg white indicators have been confirmed, probably, by all researchers who have studied this issue (Karoui et al, 2006;Khan et al, 2014;Lall et al, 2018;Samli et al, 2005;Tabidi, 2011).…”
Section: Introductionsupporting
confidence: 70%
“…The results also showed that the rate of change in traits values increased with increased storage periods. Several investigators stated similar storage length effect with respect to Haugh unit values and yolk index Haugh unit values and yolk index (Drabik et al, 2018;Lall et al, 2018;Samli et al, 2005;Yildirim, 2017), yolk color grade (Lee et al, 2016), yolk albumin ratio (Hermiz et al, 2012;Moula et al, 2009), yolk and albumin pH (Drabik et al, 2018) , specific gravity and air cell depth (Alsobayel & Albadry, 2011;Samli et al, 2005) and shell thickness ( Khatun et al, 2016;Monira et al, 2003). In dissimilarity to our results, some investigators reported that the storage period had no effect regarding the yolk color grade (Alsobayel & Albadry, 2011;Stojčić & Perić, 2018), yolk albumin ratio (Khatun et al, 2016), albumin pH (Lee et al, 2016) shell thickness and shell surface area (Yildirim 2017).…”
Section: Discussionmentioning
confidence: 98%
“…In dissimilarity to our results, some investigators reported that the storage period had no effect regarding the yolk color grade (Alsobayel & Albadry, 2011;Stojčić & Perić, 2018), yolk albumin ratio (Khatun et al, 2016), albumin pH (Lee et al, 2016) shell thickness and shell surface area (Yildirim 2017). However, some other investigators reported that the storage period led to a significant increase regarding the shell weight per unit of surface area (Alsobayel & Albadry, 2011), shell density (Lee et al, 2016;Alsobayel & Albadry, 2011), and shell thickness (Lall et al, 2018) and decrease in yolk color grade (Kralik et al, 2014;Drabik et al, 2018), with increased storage period. The differences between our results Alshaikhi AM, Abdullatif AA, Badwi MA, Alsobayel AA…”
Section: Discussionmentioning
confidence: 99%